Socio-Technical Aspects Of Electronic Medical Record Use Related To Patient Safety At Prof Dr. R. D. Kandou Manado Hospital - Adhistya, Maya; Kekenusa, John S.; Sinolungan, Jehosua S.V. (Neo Journal of economy and social humanities, 2023)
In the current era of industrial digitalization 4.0, the use of information and communication technology has been widely adopted by various sectors, including the health sector. Electronic Medical Records (RME) is one form of information technology that has been recognized to have an impact on increasing patient satisfaction, documentation accuracy, accelerating data access and reducing clinical errors, but on the other hand, some emerging empirical evidence shows that health information technology can cause new problems related to patient safety. Socio-technical aspects of RME use such as user behavior, poor system design and lack of supporting infrastructure were identified to compromise patient safety. This study used mixed methods with a sequential explanatory design, which was conducted at Prof. Dr. R.D. Kandou Hospital Manado in February-May 2023. Quantitative research was conducted by distributing questionnaires to RME users, namely doctors, nurses, midwives and other health workers with a sample of 324 respondents taken by proportional stratified random sampling technique, while qualitative research was conducted by interview, observation and documentation with the role of the researcher as a human instrument. The results showed that there was a significant relationship between patient safety and user behavior (r=0.611), system design (r=0.702) and the condition of RME supporting facilities (r=0.529). To prevent the occurrence of patient safety incidents as a result of the use of RME, basic IT training and mastery of RME features for users must be improved, continuously conducting user-centered RME redesign and optimizing RME supporting infrastructure.